Effect of Advertisement on Buying Behavior of OTC Medicines in Nepalese Context - Tiwari, Pankaj Kumar (Journal of Advanced Academic Research, 2017)
Buying of OTC medicines is the self-medication practice. From the very ancient period, people used different types of herbs for the treatment of their health problems. In the changing practice of human life, people modern treatment took over. Advertisement has become the fastest marketing communication to disseminate the message in the global society. In this connection, the study is going to identify the effect of advertisement on buying behavior of OTC medicines in Nepalese context. The study was based on the descriptive design. Data was collected from the 400 OTC consumers by using the structured questionnaire survey. Systematic random sampling technique was used to select the respondents. The study found that 41.2% people were aware through the advertisement of OTC medicines whereas only 32% had purchased the OTC medicine after watching the advertisement. Similarly, only 14.8% reported that they were influenced by the advertisement and 46% said that advertisement of OTC medicine had positive effect on the people as people are well informed regarding the medicines through such advertisements. It helped to sensitize the people. Study found that there was positive contribution of advertisement to disseminate the message but not so effective to change the buying behavior of consumer. Only 6.8% people believe in the advertisement done through the television or print media. People mostly rely on the recommendation of doctors or pharmacists in Nepalese context. Thus, pharmaceutical companies can use the pharmacists for the effective advertisement and sales of OTC medicines.